The quantity and quality of children: A semi-parametric Bayesian IV approach - Sylvia Frühwirth-Schnatter; Martin Halla; Alexandra Posekany; Gerald J. Pruckner; Thomas Schober (Johannes Kepler University of Linz, Department of Economics, 2014)
Prior empirical research on the theoretically proposed interaction between the quantity and the quality of children builds on exogenous variation in family size due to twin births and focuses on human capital outcomes. The typical finding can be described as a statistically nonsignificant two-stage least squares (2SLS) estimate, with substantial standard errors. We regard these conclusions of no empirical support for the quantity-quality trade-off as premature and, therefore, extend the empirical approach in two ways. First, we add health as an additional outcome dimension. Second, we apply a semi-parametric Bayesian IV approach for econometric inference. Our estimation results substantiate the finding of a zero effect: we provide estimates with an increased precision by a factor of approximately twenty-three, for a broader set of outcomes.
Keywords: J13; C26; C11; I20; J20; I10; 330; quantity-quality model of fertility; family size; human capital; health; semi-parametric Bayesian IV approach